2000
DOI: 10.1073/pnas.100501197
|View full text |Cite
|
Sign up to set email alerts
|

Myogenic stem cell function is impaired in mice lacking the forkhead /winged helix protein MNF

Abstract: Myocyte nuclear factor (MNF) is a winged helix transcription factor that is expressed selectively in myogenic stem cells (satellite cells) of adult animals. Using a gene knockout strategy to generate a functional null allele at the Mnf locus, we observed that mice lacking MNF are viable, but severely runted. Skeletal muscles of Mnf؊͞؊ animals are atrophic, and satellite cell function is impaired. Muscle regeneration after injury is delayed and incomplete, and the normal timing of expression of cell cycle regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
155
1
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 149 publications
(164 citation statements)
references
References 35 publications
(59 reference statements)
5
155
1
3
Order By: Relevance
“…In other models, using crushing, 27 freezing, 9 or chemically induced injuries to skeletal muscle 12 to study satellite cell activation, proliferation and regeneration, two response of satellite cells to activation have been described. These are based on the integrity of the basal lamina.…”
Section: Discussionmentioning
confidence: 99%
“…In other models, using crushing, 27 freezing, 9 or chemically induced injuries to skeletal muscle 12 to study satellite cell activation, proliferation and regeneration, two response of satellite cells to activation have been described. These are based on the integrity of the basal lamina.…”
Section: Discussionmentioning
confidence: 99%
“…Primers for real-time and semiquantitative RT-PCR were: p27, For 5Ј-TTGGGTCTCAGGCAAACTC-T-3Ј; p27, Rev 5Ј-TCTGTTCTGTTGGCCCTTTT-3Ј; p53, For 5Ј-AAGT-CCTTTGCCCTGAACTG-3Ј; p53, Rev 5Ј-CTGTAGCATGGGCATCCTT-T-3Ј; p21, For 5Ј-TTGCACTCTGGTGTCTGAGC-3Ј; p21, Rev 5Ј-CTGC-GCTTGGAGTGATAGAA-3Ј; cyclin B1, For 5Ј-AACCTGAGCCTGAAC-CTGAA-3Ј, cyclin B1, Rev 5Ј-GCGTCTACGTCACTCACTGC-3Ј; cyclin D1, For 5Ј-CGGATGAGAACAAGCAGACC-3Ј; cyclin D1, Rev5Ј-GCAG-GAGAGGAAGTTGTTGG-3Ј; p57, For 5Ј-AGGAGCAGGACGAGAATC-AAG-3Ј; p57, Rev 5Ј-ACATGAACGAAAGGTCCCAG-3Ј; cdk1, For 5Ј-G-GTCCGTCGTAACCTGTTGA-3Ј; cdk1, Rev 5Ј-CTCCTTCTTCCTCGC-TTTCA-3Ј; glyceraldehyde-3-phosphate dehydrogenase, For 5Ј-GTGG-CAAAGTGGAGATTGTTGCC-3Ј; glyceraldehyde-3-phosphate dehydrogenase, Rev 5Ј-GATGATGACCCGTTTGGCTCC-3Ј. Western analysis of protein extracts isolated from wild type or Foxk1Ϫ/Ϫ progenitor cell cultures was performed as described previously using rabbit anti-p21 or rabbit anti-p53 sera (1:1000 dilution, Santa Cruz Biotechnologies) (15).…”
Section: Real-time Rt-pcr Semiquantitative Rt-pcr and Westernmentioning
confidence: 99%
“…Cardiotoxin Injury of Mouse Skeletal Muscle-Gastrocnemius muscles from WT, Foxk1Ϫ/Ϫ, and Foxk1Ϫ/Ϫ:p21 CIP Ϫ/Ϫ mice (2-month-old) were injected with cardiotoxin (150 l/muscle of 10 M cardiotoxin (Naja nigricollis; Calbiochem)) (15). Muscles were harvested 10 days post-injection and fixed overnight with 4% paraformaldehyde.…”
Section: Real-time Rt-pcr Semiquantitative Rt-pcr and Westernmentioning
confidence: 99%
See 1 more Smart Citation
“…Several satellite cell markers have also been identified. Among them are paired box transcription factors Pax3 and Pax7 (Seale and Rudnicki, 2000;Relaix et al, 2006); c-met, the receptor for hepatocyte growth factor (HGF; Cornelison and Wold, 1997); myocyte nuclear factor (MNF; Hawke and Garry, 2001;Garry et al, 2000); Mcadherin, a calcium-dependent cell adhesion molecule (Irintchev et al, 1994;Moore and Walsh, 1993); vascular cell adhesion molecule 1 (VCAM1; Rosen et al, 1992); neural cell adhesion molecule (N-CAM; Illa et al, 1992); CD34, a hematopoietic stem cell marker (Beauchamp et al, 2000); and heparan sulfate proteoglycans Syndecan 3 and 4 (Cornelison et al, 2001). It has been clearly demonstrated that activation, proliferation, and differentiation of satellite cells after injury are controlled by members of the myogenic regulatory factor (MRF) family, in a similar manner to muscle precursor cells during embryonic development.…”
Section: Molecular Markersmentioning
confidence: 99%